1983
DOI: 10.1038/hdy.1983.40
|View full text |Cite
|
Sign up to set email alerts
|

Clonal diversity in populations of Daphnia pulex reproducing by obligate parthenogenesis

Abstract: SUMMARYAllozyme studies of Daphnia pulex populations in southern Ontario revealed marked Hardy-Weinberg deviations, complete gametic phase imbalance, and high heterozygosity values. These genotypic characteristics reflect the loss of sexual reproduction; individuals reproduce by obligate parthenogenesis. Thirtynine clones were identified in the twenty-one habitats surveyed; a few of these clones retained the ability to produce male offspring. Several clones were present in many habitats, but most of the thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
123
2

Year Published

1987
1987
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 26 publications
4
123
2
Order By: Relevance
“…The present study has made it clear that F1 hybrids between D. pulex and D. pulicaria are common at sites across Canada and reproduce asexually. Their prevalance in western Canada was not unexpected in light of their predominance in grassland pools in the Great Lakes region (Hebert & Crease, 1983). Whereas the initial conclusion concerning the hybrid origin of these clones was based on the results of allozyme surveys ( Hebert et al,198 9a), this conclusion has recently been supported by rDNA analysis (Crease & Lynch, 1991).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The present study has made it clear that F1 hybrids between D. pulex and D. pulicaria are common at sites across Canada and reproduce asexually. Their prevalance in western Canada was not unexpected in light of their predominance in grassland pools in the Great Lakes region (Hebert & Crease, 1983). Whereas the initial conclusion concerning the hybrid origin of these clones was based on the results of allozyme surveys ( Hebert et al,198 9a), this conclusion has recently been supported by rDNA analysis (Crease & Lynch, 1991).…”
Section: Discussionmentioning
confidence: 64%
“…Recent work established the presence of F1 hybrids between these species and has shown that such hybrids always reproduce by obligate parthenogenesis (Hebert et a!., 1989a;Crease & Lynch, 1991). Earlier studies incorrectly classified these hybrids as asexual clones of D. pulex (Hebert & Crease, 1983;Lynch 1983;Innes et al, 1986). It remains clear, however, that D. pulex s.s. shows variable reproductive behaviour, with some populations reproducing by cyclic and others by obligate parthenogenesis.…”
Section: Introductionmentioning
confidence: 87%
“…Recent studies (Hobaek et al, 1993;Ward et al, 1994) have shown that populations of D. pulex from Eurasia have a similarly low level of clonal diversity (1.5 and 1.7 clones per pond). Higher clonal diversity estimates have however been reported for D. middendorffiana from a high-arctic site (4.5 clones per pond) and for D. pulex from a temperate zone region (2-4 clones per pond) (Hebert & Crease, 1983; (Weider & Hebert, 1987a;Zhao & King, 1989;Browne, 1992;Wilson & Hebert, 1992). Reasons for the differential distribution of the D. tenebrosa clones are not clear.…”
Section: Mtdna Analysismentioning
confidence: 97%
“…Allozyme analyses have shown that clonal diversity is very high in these obligate parthenogens with thousands of clones occurring over the species distribution. However, single habitats typically contain fewer than three clones in both temperate and lowarctic sites (Hebert & Crease, 1983;Weider & Hebert, 1987a;Wilson & Hebert, 1992). Higher levels of clonal diversity (an average of 4.5 clones per pond) have been found at a high-arctic site occupied almost exclusively by polyploid clones (Weider et a!., 1987).…”
mentioning
confidence: 99%
“…Among obligate parthenogens, multiple clones are often present within local populations. For example, Hebert and Crease (1983) observed 22 clones of obligately parthenogenetic Daphnia pulex from ponds near Windsor, Ontario. Clonal diversity estimates for a single habitat (pond) ranged from [1][2][3][4][5][6][7] clones/pond (mean = 40 clones/pond based on 4 enzyme loci).…”
Section: Introductionmentioning
confidence: 99%